1979
DOI: 10.1139/o79-005
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical and cytochemical localization of acetylcholinesterase in retina and optic tectum of teleost fish

Abstract: The activity of cholinesterase and its cellular and subcellular localization were investigated in the retina and optic tectum of Eugerres plumieri and in the retina of Carassius carassius by means of radiometric, histochemical, and cytochemical procedures. In both fishes only the presence of acetylcholinesterase could be demonstrated. This study, besides confirming previous findings that acetylcholinesterase is located in the ganglion and amacrine cells of the retina as well as in the inner plexiform layer, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1980
1980
1991
1991

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The cellular localization of AchE activity in the carp retina was consistent with earlier findings (4,9,29,31). AchE activity was found in a certain group of amacrine cells and in some ganglion cells, diffusely in the IPL and weakly in the external horizontal cell layer.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The cellular localization of AchE activity in the carp retina was consistent with earlier findings (4,9,29,31). AchE activity was found in a certain group of amacrine cells and in some ganglion cells, diffusely in the IPL and weakly in the external horizontal cell layer.…”
Section: Discussionsupporting
confidence: 91%
“…The cellular localization of AchE and the Ach metabolism in the retina have been also extensively investigated (4,9,29,31). It has been commonly described that AchE activity is predominantly positive in amacrine and ganglion cells and at the IPL.…”
mentioning
confidence: 99%
“…However, it is unlikely that AChE is confined to presynaptic elements. Electron microscope (EM) histochemistry of the tectum of the Mojarra (Eugerres plumieri) shows reaction product on dendritic and axonal membranes as well as on nerve terminals (Drujan et al, 1979);Villani et al (1979), using similar methods, also concluded that all neuronal types in the optic tectum synthesized AChE.…”
Section: Neurotransmitters and Neuromodulatorsmentioning
confidence: 99%
“…A number of investigators have also studied the enzyme distribution within the retina during its development (5,30,31). These studies have revealed that AChE activity localizes in ganglion and amacrine cells, and in the inner plexiform layer of almost all species so far examined (5,10,12,19,20,25,28). In addition, the presence of enzyme activity has been reported within the horizontal cells of the rat (31), rabbit (28), chick (30) and fish (10), and within the outer plexiform layer of the frog (5), newt (8) and fish (10).…”
Section: Acetylcholinesterasementioning
confidence: 99%